Productive performance of canchim and nelore females. II. first calving - Alencar, Maurício Mello de; Bugner, Manfred (Pesquisa Agropecuaria Brasileira, 2014)
This work presents the results of ego and weight at first calving of a study undertook to compare the Canchim and Nelore beef cattle breeds. It was shown that sex of calf had no effect on age at first calving and on gestation length, while day of parturition showed a quadratic effect (P
Keywords: age; weight; gestation length